Associated Factors of Father Involvement in Stunting Prevention in Toddlers Based on Transcultural Nursing Theory - Superzeki Zaidatul Fadilah; Dwi Indah Lestari; Ishana Balaputra (Jurnal Kesehatan, 2024)
Stunting is still one of the most pressing global health problems. Father involvement in childcare is needed to ensure optimal child growth and development and free the child from stunting problems. Based on transcultural nursing theory, this study analyzes factors related to father involvement in preventing toddler stunting. The study used a cross-sectional approach with a multistage random sampling technique in Jember Regency with a sample of 852 respondents. A questionnaire was used to collect data. The study was conducted for 2 weeks, from August 1, 2024, to August 15, 2024. Statistical tests were carried out using Spearman Rho with a significance of 95% (α <0.05). Statistical analysis showed that technology factors (p-value=<0.001, r score=0.297), religion, spirituality, and philosophy (p-value=<0.001, r score= 0.170; kinship and social (p-value=<0.001, r score= 0.378),  cultural values, beliefs, and lifestyles (p-value=<0.001, r score=0.204); politics and law(p-value=<0.001, r score=0.360);  economics (p-value=<0.001, r score=0.370)—were positively correlated with father involvement in preventing stunting in toddlers. Meanwhile, biological variables (p-value=0.054, r score=0.237) and education level (p-value=-0.067, r score=0.052) did not correlate significantly with the father's involvement in preventing toddler stunting. Current research shows that father involvement in preventing stunting in toddlers is beneficial. Public health nurses can use these results to create health promotion initiatives that encourage fathers to be more involved in child care and prevent childhood stunting. The results of this study can be used to develop health promotion programs to increase father involvement in improving stunting prevention.